Effects of two personalized dietary strategies during a 2‐year intervention in subjects with nonalcoholic fatty liver disease: A randomized trial. (1st March 2021) - Marin‐Alejandre, Bertha A.; Cantero, Irene; Perez‐Diaz‐del‐Campo, Nuria; Monreal, Jose I.; Elorz, Mariana; Herrero, Jose I.; Benito‐Boillos, Alberto; Quiroga, Jorge; Martinez‐Echeverria, Ana; Uriz‐Otano, Juan I.; Huarte‐Muniesa, Maria P.; Tur, Josep A.; et al.
Abstract: Background and objectives: Nonalcoholic fatty liver disease (NAFLD) management is focused on lifestyle modifications, but long‐term maintenance is a challenge for many individuals. This study aimed to evaluate the long‐term effects of two personalized energy‐restricted dietary strategies on weight loss, metabolic and hepatic outcomes in overweight/obese subjects with NAFLD. Methods: Ninety‐eight subjects from the Fatty Liver in Obesity (FLiO) study (NCT03183193) were randomly assigned to the American Heart Association (AHA) or the FLiO dietary group in a 2‐year controlled trial. Anthropometry, body composition (DXA), biochemical parameters and hepatic status (ultrasonography, Magnetic Resonance Imaging, and elastography) were assessed at baseline, 6, 12 and 24 months. Results: Both the AHA and FLiO diets significantly reduced body weight at 6 (−9.7% vs −10.1%), 12 (−6.7% vs −9.6%), and 24 months (−4.8% vs −7.6%) with significant improvements in body composition, biochemical and liver determinations throughout the intervention. At the end of the follow‐up, the FLiO group showed a greater decrease in ALT, liver stiffness and Fatty Liver Index, among others, compared to AHA group, although these differences were attenuated when the analyses were adjusted by weight loss percentage. The FLiO group also showed a greater increase in adiponectin compared to AHA group. Conclusions: The AHA and FLiO diets were able to improve body weight and body composition, as well as metabolic and hepatic status of participants with overweight/obesity and NAFLD within a 2‐year follow‐up. These findings show that both strategies are suitable alternatives for NAFLD management. However, the FLiO strategy may provide more persistent benefits in metabolic and hepatic parameters.